For social peace in Brazil : industrialists and the remaking of the working class in São Paulo, 1920-1964 - Weinstein, Barbara (University of North Carolina Press, 1996)
"Outstanding history of São Paulo industrialists' attempt to modernize industry by remaking the working class. Based on a wide range of documents, the work focuses on vocational training programs sponsored by the state-chartered, but industry-run, Serviço Nacional de Aprendizagem Industrial and on the industrial social services institute, Serviço Social da Indústria, from 1940s-1960s. Argues that workers and industrialists converged on rationalizing project of improving workers' skills, but diverged on politics where workers followed populists and industrialists conspired for more managerial, authoritarian government. Essential contribution to history of relationships between labor, elites, and state, revising arguments such as Cardoso's that Brazilian bourgeoisie lacked a 'project.'"--Handbook of Latin American Studies, v. 58.